2018
DOI: 10.5946/ce.2017.155
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Features of Mucous Cap Polyps: A Way to Predict Serrated Polyps

Abstract: Background/AimsThe aims of the study were to identify whether a mucous-cap predicts the presence of serrated polyps, and to determine whether additional endoscopic findings predict the presence of a sessile serrated adenomas/polyp (SSA/P). MethodsWe analyzed 147 mucous-capped polyps with corresponding histology, during 2011–2014. Eight endoscopic features (presence of borders, elevation, rim of debris, location in the colon, size ≥10 mm, varicose vessels, nodularity, and alteration in mucosal folds) of mucous-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 32 publications
(75 reference statements)
0
6
0
Order By: Relevance
“…Considering a reported higher sensitivity of dark spots than that in our study, chromoendoscopy is necessary to identify accurately the pit pattern. Some studies have reported that a mucus cap is a good indicator of SSA/P, whereas in our study only 20.4% of SSA/P presented with this feature, which is probably due to the thorough rinsing we performed during the colonoscopy. Although careful irrigation is important for screening colorectal diseases to obtain a good view of the lesions, observation before rinsing is also of great importance for detecting SSA/P.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering a reported higher sensitivity of dark spots than that in our study, chromoendoscopy is necessary to identify accurately the pit pattern. Some studies have reported that a mucus cap is a good indicator of SSA/P, whereas in our study only 20.4% of SSA/P presented with this feature, which is probably due to the thorough rinsing we performed during the colonoscopy. Although careful irrigation is important for screening colorectal diseases to obtain a good view of the lesions, observation before rinsing is also of great importance for detecting SSA/P.…”
Section: Discussionmentioning
confidence: 99%
“…Before the evaluation, five endoscopic features under NBI were determined as follows: (a) dark spots, defined as dilated crypt openings inside the crypts that are at least twice larger than the surrounding normal mucosa and were thought to be type II‐O pits after being sprayed with dye; (b) a clouded surface, defined as a mild, nodule‐like surface which resembles accumulated cumulus clouds; (c) a mucus cap, defined as an accumulation of mucus on the surface of a lesion, including clear and bile‐stained mucus, which can be easily removed after rinsing; (d) DBV, defined as thickened capillary vessels with branching presenting on the surface of the lesions that differ from the “meshed capillary vessels” in the CP classification; and (e) CP classification. Typical images of these five endoscopic features are shown in Figure .…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, polyps occur elsewhere in the body where there is a mucous membrane. The presence of polyps and accompanying mucosal edema is one of the main observations at examination [82]. The polyps may be involved in chronic sinusitis.…”
Section: Nasal Polypsmentioning
confidence: 99%
“…In a current issue of Clinical endoscopy , Moy et al investigated whether a mucous- capped polyp, one of the most common endoscopic features of SSA/Ps, can predict the presence of serrated polyps [ 13 ]. They examined the endoscopic features of 147 mucous-capped polyps to determine if they could predict SSA/Ps.…”
mentioning
confidence: 99%
“…They examined the endoscopic features of 147 mucous-capped polyps to determine if they could predict SSA/Ps. Among these, there were 127 (86%) serrated polyps (right-sided hyperplastic polyps, SSA/Ps, or traditional serrated adenomas), and only 43 (29%) SSA/Ps [ 13 ]. To find the predictive features of SSA/Ps, they also evaluated other endoscopic characteristics of mucous- capped polyps such as polyp size (≥10 mm), the distinct border, elevation, rim of debris, location, varicos vessels, nodular surface and alterations in the fold contour.…”
mentioning
confidence: 99%